Environmental education or education for sustainable development? The ethical sense of environmental education - Castro-Carpio, Augusto (2023)
Since the 1960s it has become clear that a development model focused on economic growth would erode environmental systems (through pollution, deforestation, soil degradation, climate change, loss of biodiversity, etc.) and exacerbate social conflicts (through violence, migration, poverty, food insecurity and other phenomena). As mechanisms to help reverse the damage and balance the relationship with nature, the United Nations formulated educational strategies aimed at harmonizing the relationships of human beings with the environment. Initially they spoke of environmental education and in later years education for sustainable development. This article reflects on the international perspective on issues such as development, sustainability, and environmental education to then dive into the concept of environmental education and its various interpretations. Furthermore, it enters the debate on “education for sustainable development” to bring out the most significant vicissitudes in the understanding of development. Finally, it addresses the importance of environmental education at school and underscores the relevance of ethics in the approach to that environmental education.